PENERAPAN LEAN MANAGEMENT PADA PROSES OPERASIONAL SEKOLAH/INSTITUSI PELATIHAN UNTUK MENINGKATKAN EFISIENSI - Jopinus Saragih; Margono Margono; Reno Triwan Padang (Nusantara Hasana Journal, 2025)
This Community Service (PkM) program aims to improve the operational efficiency of schools and training institutions through the implementation of Lean Management to reduce waste, speed up services, and standardize processes. Common issues faced by partner institutions include long administrative service lines, duplicate data entry, lengthy document approval wait times, slow procurement and infrastructure processes, and procedural variations across units. The program is implemented through process mapping (Value Stream Mapping), identification of the 8 types of lean waste, root cause analysis, design of the future state process, development of SOPs and visual management, implementation of 5S, and piloting of quick improvements (Kaizen) on priority processes. Outputs include before-and-after process maps, standardized SOPs, performance indicators (lead time, cycle time, first-time-right), and a plan for continuous improvement.